Non-suicidal self-injury in patients with eating disorders: nuclear aspects (Colombia Medica, 2021)
Background: Through the culture of thinness, increasingly promoted in our society as a beauty canon, it is not surprising that the number of people affected by eating disorders is increasing.Objective: This research aims to study the relationship between non-suicidal self-injuries and nuclear aspects of eating disorders specified along with this article.Methods: The sample consisted of 60 women diagnosed with anorexia and bulimia. Questionnaires assessing impulsivity, body satisfaction, alexithymia, body attitude and self-esteem were administered. Participants with non-suicidal self-harm were compared with those without, and participants with anorexia with and without self-harm and participants with bulimia with and without self-harm were compared. Results: Differences were found in body dissatisfaction  = 5,71; p ≤ ,01), body attitudes  = 4,80; p ≤ ,02), self-esteem  = 14,09; p ≤ .00) and impulsivity (t = 3,39; p ≤ ,01) between participants with and without non-suicidal self-harm.Conclusions: These are key factors for the clinic in the treatment of eating disorders to prevent the presence of self-harm, as it allows focusing the treatment target on those aspects such as dissatisfaction and impulsivity, which are key in the development of self-harm.